Mesenteric adipose tissue in Crohn’s disease alters the immune response of the ileal mucosa and increases angiogenesis and fibrosis. - Reyes Martín, Flores; Kentaoui-Bousellam, Imane; Ruíz-Malagón, Antonio Jesús; Ho-Plágaro, Ailec; López-Gómez, Carlos; Herraiz-Vilela, Marina; Alcaín-Martínez, Guillermo; Camargo-Camero, Raquel; Martos-VanDussen, Juan Víctor; Camacho-Martel, Laura; Gutiérrez-Martínez, Fernando; Arranz-Salas, Isabel; et al. (Springer Nature, 2025)
Mesenteric adipose tissue (MAT) may be involved in the pathogenesis of Crohn's disease (CD). However, its precise role remains uncertain. We analize the profile of molecules secreted by the MAT (secretome) in CD, differentiating between 'creeping fat' (CD-CrF) and the MAT obtained from a non-affected area (CD-NA), and to characterise its impact on the healthy ileum. The immune cell infiltration was higher in MAT from CD, particularly in CrF, compared to control-MAT. CD-NA and CD-CrF secretomes exhibited an increase of cytokines, immuno-checkpoints and other serum markers. A second profile included an increase in growth factors only in CD-CrF secretome. CD-NA and CD-CrF secretomes demonstrated enhanced myofibroblast wound healing and endothelial cell tube formation. On healthy human ileum, CD-NA and CD-CrF secretomes led to a down-regulation of genes related to antigen presentation to T cells, the major histocompatibility complex class II and the Th2 and Th17 cell differentiation. In conclusion, the profile of MAT secretome is different in CD patients, and their effects on the ileum, specially those of CrF, suggest a modification of the adaptive immune response, and a more pro-angiogenic and pro-fibrotic profile. MAT seems to have a significant role in the pathogenesis of CD.
Keywords: Inmunopatología; Respuesta inmune; Neovascularización; Enteritis regional; Enfermedad inflamatoria intestinal; Tejido adiposo; Adipose tissue; Angiogenesis; Crohn’s disease; Fibrosis; Ileum; Immune response; Immunopathology